Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Pada Rsud Hadji Padjonga Daeng Ngalle Kabupaten Takalar - Wahyuni, Sri; Hakim, Lukman; Malik, Ihyani (Universitas Muhammadiyah Makassar, 2021)
This study aimed to determine how the influence of organizational culture variables on employee performance variables at Hadji Padjonga Daeng Ngalle Hospital, Takalar Regency. This study used quantitative research methods. Data were analyzed using descriptive statistics with a simple linear regression formula. Then the data was explained in the form of tables, frequencies, pictures, and narrative processed data with the help of IBM SPSS Version 22. The results of this study showed that there was an insignificant influence of organizational culture on employee performance. From the analysis, it concluded that organizational culture had a very weak influence on employee performance, this could be seen from the results of the determination test, it was known that the R2 value was 0.048, which meant 4.8%, which indicated that organizational culture was influenced by employee performance and the rest was influenced by other variables. Which meant the values in organizational culture such as: individual initiative, tolerance for risk, supervision, management support and communication patterns did not contribute to improving employee performance.Keywords: influence, organizational culture, employee performance